Effect of Mixed Probiotics on Ovalbumin-Induced Atopic Dermatitis in Juvenile Mice - Jinli Huang; Xingzhi Wang; Qiuhong Li; Panpan Zhang; Zenghui Jing; Juan Zhang; Hui Su; Xin Sun (International Journal of Microbiology)
Atopic dermatitis is one of the most common dermatologic problems, especially in children. Given the ability of symbiotic microorganisms in modulating the immune system, probiotics administration has been studied in previous research in the management of atopic dermatitis. However, there are conflicting results between studies. In this study, we aimed to assess the effectiveness of mixed probiotics as a treatment option for atopic dermatitis induced by ovalbumin. BALB/c juvenile mice were classified and divided into the ovalbumin group, mixed probiotic group (ovalbumin + LK), and control group. Except for the control group, all mice were sensitized with ovalbumin to establish a model of atopic dermatitis. The mixed probiotics were given by gavage for 14 days. Mice body weight, skin lesions, skin inflammation, ovalbumin-specific Ig, the number of Treg and CD103+DC, and the expression level of PD-1/PD-L1 were examined. The results showed that mixed probiotics can improve body weight and alleviate skin symptoms. Mixed probiotics reduced serum Th2 inflammatory factors, eosinophils, mast cell degranulation, mast cell count, and the expression of ovalbumin-specific immunoglobulin E/G1 and increased the anti-inflammatory cytokine interleukin-10, Treg cells, CD103+DC cells, and the expression level of PD-1/PD-L1. These findings suggest that mixed probiotics could be a viable treatment option for atopic dermatitis and provide insight into the underlying mechanisms involved.